Nanoparticle characterization of Er-doped SnO2 pellets obtained with different pH of colloidal suspension - Ravaro, Leandro P. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Tabata, Américo Sheitiro [UNESP]; Pontes, Fenelon Martinho Lima [UNESP]; Oliveira, José Brás Barreto de [UNESP] (AIP Publishing, 2013)
SnO2:2 at. %Er xerogel samples were obtained by sol-gel technique from colloidal suspensions with distinct pHs. The evaluation of critical regions inside the nanocrystallite is fundamental for the interpretation of the influence of pH on the emission data. In this way, the nanocrystal depletion layer thickness was obtained with the help of photoluminescence, Raman, X-ray diffraction, and field-emission gun scanning electron microscopy measurements. It was observed that acid suspensions (pH < 7) lead to high surface disorder in which a larger number of cross-linked bonds Sn-O-Sn among nanoparticles are present. For these samples, the nanoparticle depletion layer is larger as compared to samples obtained from other pH. Photoluminescence measurement in the near infrared region indicates that the emission intensity of the transition 4I13/2 → 4I15/2 is also influenced by the pH of the starting colloidal suspension, generating peaks more or less broadened, depending on location of Er3+ ions in the SnO2 lattice (high or low symmetry sites). © 2013 AIP Publishing LLC.
Keywords: Colloidal suspensions; Depletion-layer thickness; Emission intensity; Field emission guns; Near infrared region; Photoluminescence measurements; Sol-gel technique; Surface disorder; Erbium; Nanoparticles; Photoluminescence; Scanning electron microscopy; Sol-gels; Tin; X ray diffraction; Suspensions (fluids)